Empirical Study on the Work Life Balance Issues of Chef at Supervisory Level in Hotels of Delhi - Khanna, Kavita; Bali, Paresh (International Research Journal of Management, IT & Social Sciences, 2017)
The objective of the research was to find out work life balance issues for chefs at supervisory level in Hotels of Delhi. The supervisory level chefs are very critical to fulfill the requirement of the smooth operations for the different section of the kitchen or food production department. Supervisors have to monitor, guide and motivate the operative staff of any department or process; this becomes more important if it is food production department of a hotel. The objective of the study was to find out whether there exists a healthy work life balance in lives of supervisory chefs engaged in hotels of Delhi. The paper also try to evaluate the work life balance on the four dimensions of work life balance namely quality time, involvement, satisfaction and health. The study tries to analyze and identify the probable causes for work life imbalance and expected solutions for the improvement of work life balance. The author had devised a questionnaire to gather the data from the respondents, which included a set of statement on which participants agreement or disagreement was recorded. Based on the responses scores for each dimension were calculated and integrating the scores the overall levels for work life balance were ascertained. Study employed SPSS 18 for analysis of data, where data was analyzed using cross tables, descriptive statistics & t test to come to conclusions. The reliability for the questionnaire was ascertained through Cronbach alpha and coefficient of correlations. The results had clearly reflected that chefs at supervisory level have work life balance issues as their mean score is less than the average for all the dimensions also on overall score for work life balance the data clearly proves that the chefs at supervisory levels have low levels. The main causes which were found for work life imbalance were stretched working hours, break shifts, long travelling time and inability to get leaves. The main probable solutions identified to improve the levels of work life balance were increased salary, to compensate for actual hours of work, ease of getting leaves.